SEMIOTIC ANALYSIS OF CHARLIE LYNDSAY’S GENDER TRANSFORMATION IN REBEKAH FORTUNE’S FILM “JUST CHARLIE” - Nurul Aisy, Sarah Azizah Nurul Aisy1; Halim, Abd; Iskandar, Iskandar (State University of Makassar, 2025)
This research aim to analyse the representation of gender transformation in Rebekah Fortune’s film Just Charlie through a semiotic approach. Utilizing Roland Barthes’ semiotic theory and supported by Judith Butler’s concept of gender performativity, this research analyzes the verbal and non-verbal signs that signify the main character Charlie Lyndsay’s journey as a transgender individual. The analysis focuses on visual elements such as clothing, gestures, and intimate moments, as well as verbal expressions that reveal the character’s inner struggles and journey toward self-discovery. The findings reveal that Just Charlie deconstructs traditional binary notions of masculinity and femininity by portraying gender as a fluid and performative construct. Key visual and verbal elements in the film challenge societal norms and highlight the tension between societal expectations and personal authenticity. This research contributes to discussions on transgender representation in media, offering insights into how semiotic tools in film can foster greater awareness and understanding of diverse gender identities.Keywords: Gender transformation, Semiotics, Gender performativity, Just Charlie